Advancing analysis of biofuel precursors from lignin: complete molecular characterization using GC × GC-FID - Linyu Zhu; Miloš Auersvald; Cunhao Cui; Yuhe Liao; Jing Zhang; Qing He; Lingfeng Li; Yi Ouyang; Zhongyue Zhou; Fei Qi; Kevin M. Van Geem (Fuel, 2026)

Substantial mitigation of nitrous oxide realized in a light-mediated and aeration-free microalgal-bacterial consortium system - Lingfeng Wang; Weican Shi; Yanlin Liu; Zhaoming He; Jianhua Guo; Shijian Ge; Shuang Qiu (Algal Research, 2026)

Reverse flotation desilication of bauxite Ore: unraveling the mechanism of Cu(II)-SDSo in selective separation of kaolinite from diaspore - Boai Zhang; Lingfeng Shen; Honghu Tang; Jianjun Wang; Wei Sun; Jianyong He; Li Wang (Minerals Engineering, 2026)

Humic acid facilitates microbial manganese oxidation-driven arsenic remediation in soil across a wide temperature range - Weiwei Zhai; Wenjin Zhang; Lingfeng Dong; Yulong Ru; Yao Xu; Zhanfei He; Daoyong Zhang; Xiangliang Pan (Journal of Environmental Management, 2026)

The sea level rise of the 8.2 ka event simulated by the iCESM1.3 - Lingfeng Wan; Zhengyu Liu; Chengfei He; Chenyu Zhu; Shaoqing Zhang; Jiuyou Lu; Zhaowei Jing (Climate Dynamics, 2026)

Improving the efficiency of a CO2 heat pump for simultaneous heating and cooling coupled with an ambient source - Zhaoyang Yuan; Jintao He; Yonghao Zhang; Yu Yao; Hua Tian; Lingfeng Shi; Gequn Shu (International Journal of Refrigeration, 2025)

A hybrid cooling and power cogeneration scheme for broadening adaptability to distributed buildings: conceptual design, modeling, and operational assessment - Yonghao Zhang; Lingfeng Shi; Hua Tian; Jintao He; Yu Yao; Gequn Shu (Energy and Buildings, 2025)

Characteristics of phosphorus distribution and mechanisms of phosphorus release through migration and transformation in the sediments of deep-water reservoirs in mountainous areas - Lingfeng Wang; Feng Zhong; Haibo Li; Zhenbo Sun; Wenjie He (Journal of Environmental Chemical Engineering, 2025)

Microplastics magnify inhibitive effects of perfluorooctanoic acid on the marine microbial loop - Peichun Lin; Xiaokun Liu; Zuyuan Gao; Yelinzi Yuan; Hongbin Liu; Lingfeng Huang; Zhili He; Qinglu Zeng; Shanquan Wang (Environmental Research, 2025)

Co-infection by RGNNV and V. rotiferianus in golden pompano: Insights into disease risks and immune responses - Xinshuai Li; Lingfeng Guan; Cuiyu Liu; Jinpeng Chen; Xin He; Yanwei Li; Shaowen Wang; Qiwei Qin; Min Yang (Aquaculture, 2025)

Unlocking the effects of acid/alkali-catalyzed glycerol organosolv pretreatment on lignocellulosic biorefinery: Substrate digestibility and high-quality lignin - Lingfeng Long; Dongqin He; Tao Zhang; Xiaoxiao Chen; Xianzhi Meng; Arthur J. Ragauskas; Chen Huang (Bioresource Technology, 2025)

Response of nitrifiers to gradually increasing pH conditions in a membrane nitrification bioreactor: Microbial dynamics and alkali-resistant mechanism - Weican Shi; Zhaoming He; Jiahui Lu; Lingfeng Wang; Jianhua Guo; Shuang Qiu; Shijian Ge (Water Research, 2025)

Impact performance of curved double arrow and stacked Miura-ori panels - Zhejian Li; Lingfeng Wang; Ruofei Yan; Yuanpeng He; Hong Hao; Yuanzheng Lin; Wensu Chen (Engineering Structures, 2025)

Co-grown novel S-scheme tubular P–UCN/S-TCN homojunction mediates photocatalysis-PMS activation synergistic system for efficient degradation of antibiotic - Ting Wu; Zhifeng Liu; Binbin Shao; Yuan Pan; Qingyun He; Xiansheng Zhang; Lingfeng Zhou; Yunze Wang; Teng Li; Sheng Liu (Chemosphere, 2024)

Mapping critical soil moisture thresholds of water stress for global grasslands - Lingfeng Shi; Yanlian Zhou; Wei He; Zhoutong Dong; Zhuoyou Jiang; Yuyan Wang; Yibo Liu; Weimin Ju; Zheng Duan (Journal of Hydrology, 2024)

High pre-tension reinforcing technology and design for ultra-shallow buried large-span urban tunnels - Qi Wang; Huayong Wei; Bei Jiang; Xuepeng Wang; Lingfeng Sun; Manchao He (International Journal of Rock Mechanics and Mining Sciences, 2024)

Time-varying associations of patient and tumor characteristics with cancer survival: an analysis of SEER data across 14 cancer sites, 2004–2017 - Emily K. Roberts; Lingfeng Luo; Alison M. Mondul; Mousumi Banerjee; Christine M. Veenstra; Angela B. Mariotto; Matthew J. Schipper; Kevin He; Jeremy M. G. Taylor; Andrew F. Brouwer (Cancer Causes & Control, 2024)

Nanofiltration membrane with modified nano-gradient structure and positive charge for Li separation from high Mg/Li ratio brine - Peng Zhao; Fei Guo; Lingfeng Wang; Huange Zhen; Ning Zhang; Shaohua Yin; Guoli Zhou; Xuehua Ruan; Gaohong He; Xiaobin Jiang (Desalination, 2024)

EEG-FRM: a neural network based familiar and unfamiliar face EEG recognition method - Chao Chen; Lingfeng Fan; Ying Gao; Shuang Qiu; Wei Wei; Huiguang He (Cognitive Neurodynamics, 2024)

Impact of a gravity wave process on the upper stratospheric ozone valley on the Qinghai-Tibetan Plateau - Jundong Wang; Lingfeng Wan; Shujie Chang; Haotian He (Theoretical and Applied Climatology, 2024)
Atmospheric gravity waves are essential meso-small-scale oscillations that facilitate material exchange within the atmosphere. These waves can significantly affect the ozone layer in the Upper Troposphere and Lower Stratosphere (UTLS) on the Qinghai-Tibetan Plateau. However, the influence of gravity wave dynamic processes on upper stratospheric ozone has rarely been studied. This paper identifies the gravity waves on the Tibetan Plateau based on ECMWF Reanalysis 5 (ERA5) data, analyzes the response of the upper stratospheric ozone to the event, and simulates the dynamic propagation mechanism of gravity waves by the Weather Research and Forecasting (WRF) model. This analysis reveals that between 15:00 and 21:00 UTC on July 29, 2015, gravity waves propagated from the surface of Tibetan Plateau (450 hPa) up to the upper stratosphere (20 − 3 hPa) in an arc-shaped structure and tilted to the east with height. The gravity wave signals started to weaken at 21:00 UTC on the same day. Influenced by the easterly rapids, gravity waves partially broke near 3 hPa at 02:30 UTC on July 30, but gravity wave signals were still present, and gravity waves completely broke and released energy at 04:00 UTC. During this process, ozone in the 20–3 hPa region (upper stratosphere) on the Qinghai-Tibetan Plateau responds well to gravity waves, and the ozone mixing ratio began to drop in ozone concentration 30 min after the partial breakup (03:00 UTC). The ozone dropped drastically by about 0.014 ppmv from 04:00 to 05:00 UTC. The WRF simulation results agree well with ERA5 and accurately capture the intricate characteristics of gravity waves. Furthermore, the breakup of gravity waves caused a total drop in ozone of 0.024 ppmv.

MOF derived MnFeOX supported on carbon cloth as electrochemical anode for peroxymonosulfate electro-activation and persistent organic pollutants degradation - Xiansheng Zhang; Yuan Pan; Yunze Wang; Ting Wu; Binbin Shao; Qingyun He; Lingfeng Zhou; Teng Li; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Application of 3D hierarchical porous NiCo-spinel nanosheet array for enhancement of synergistic activation of peroxymonosulfate: Degradation, Intermediates, mechanism and degradation pathway of tetracycline - Yuan Pan; Xiansheng Zhang; Ting Wu; Binbin Shao; Teng Li; Qingyun He; Zehua Chen; Lingfeng Zhou; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Revealing the specificity of map method to predict the performance of a combined cooling and power cycle under operating conditions - Yu Yao; Lingfeng Shi; Jintao He; Xiaocun Sun; Bowen Lu; Yonghao Zhang; Hua Tian; Xuan Wang; Gequn Shu (Journal of Cleaner Production, 2023)

Molecular-level insights into the heterogeneous variations and dynamic formation mechanism of leached dissolved organic matter during the photoaging of polystyrene microplastics - Fanhao Song; Tingting Li; Jin Hur; Quan Shi; Fengchang Wu; Wei He; Di Shi; Chen He; Lingfeng Zhou; Mingqi Ruan; Yuhan Cao (Water Research, 2023)

Fabrication of immobilized lipases for efficient preparation of 1,3-dioleoyl-2-palmitoylglycerol - Lihong He; Can Zeng; Lingfeng Wei; Li Xu; Fenglin Song; Jianrong Huang; Nanjing Zhong (Food Chemistry, 2023)

Quenching-induced surface reconstruction of perovskite oxide for rapid and durable oxygen catalysise - Lingfeng Ke; Shengli Pang; Chao Long; Ting Fang; Gongmei Yang; Yifan Song; Xudong He; Shuai Ma; Yaozheng Qian; Xiangqian Shen; Chonglin Chen (Chemical Engineering Journal, 2023)

Spatio-temporal heterogeneity in the international trade resilience during COVID-19 - Wei Luo; Lingfeng He; Zihui Yang; Shirui Zhang; Yong Wang; Dianbo Liu; Sheng Hu; Li He; Jizhe Xia; Min Chen (Applied Geography, 2023)

Remediation of uranium-contaminated alkaline soil by rational application of phosphorus fertilizers: Effect and mechanism - Lingfeng Dong; Zhanfei He; Jingyi Wu; Keqing Zhang; Daoyong Zhang; Xiangliang Pan (Environmental Research, 2023)

Modelling discontinuity control on the development of Hell’s Mouth landslide - Lingfeng He; John Coggan; Doug Stead; Mirko Francioni; Matthew Eyre (Landslides, 2022)
This paper focuses on numerical modelling and back analysis of the Hell’s Mouth landslide to provide improved understanding of the evolution of a section of the north coast of Cornwall, UK. Discontinuity control is highlighted through the formation of a ‘zawn’ or inlet, the occurrence of two successive landslides and evidence of ongoing instability through opening of tension cracks behind the cliff top. Several integrated remote sensing (RS) techniques have been utilised for data acquisition to characterise the slope geometry, landslide features and tension crack extent and development. In view of the structural control on the rock slope failures, a 3D distinct element method (DEM) code incorporating a discrete fracture network and rigid blocks has been adopted for the stability analysis. The onset and opening of tension cracks behind the modelled slope failure zones has also been studied by analysing the displacements of two adjoining landslide blocks, between which, a joint-related tension crack developed. In addition, a sensitivity analysis has been undertaken to provide further insight into the influence of key discontinuity parameters (i.e. dip, dip direction, persistence and friction angle) on the stability of this section of the coastline. Numerical modelling and field observations indicate that block removal and preferential erosion along a fault resulted in the formation of the inlet. The development of the inlet provides daylighting conditions for discontinuities exposed on the inlet slope wall, triggering the initial landslide which occurred on 23 rd September 2011. Numerical modelling, and evidence from a video of the initial landslide, suggests that the cliff instability is characterised by a combination of planar sliding, wedge sliding and toppling modes of failure controlled by the discrete fracture network geometry.

Application of nanomaterials decorated with cyclodextrins as sensing elements for environment analysis - Lingfeng Gao; Chiyang He (Environmental Science and Pollution Research, 2021)

Niche overlap and divergence times support niche conservatism in eastern Asia–eastern North America disjunct plants - Xue Yin; Scott Jarvie; Wen‐Yong Guo; Tao Deng; Lingfeng Mao; Minhua Zhang; Chengjin Chu; Hong Qian; Jens‐Christian Svenning; Fangliang He (Global Ecology and Biogeography, 2021)
Aim The plant species sharing ancestors now disjunctly distributed in eastern Asia (EAS) and eastern North America (ENA) have long been a biogeographic puzzle. Species within the EAS–ENA disjunct genera are presumed to exhibit niche conservatism, the tendency of closely related species to be more ecologically similar, reflecting lineages’ common evolutionary history. However, the hypothesis has not been well examined at the species level. Location EAS and ENA. Time period Current. Major taxa studied Species within the EAS–ENA disjunct genera. Methods We compiled data on climate, species occurrence, growth form, and phylogeny to examine niche conservatism. We first built a phylogenetic tree to select intercontinental congeneric pairwise species and obtained their divergence times. We then quantified the observed niche overlaps with Schoener’s D , which has a 0–1 range, based on species occurrence and climate of species’ native ranges. To obtain projected distributions, each species’ niche was projected to the non‐native region using ensemble ecological niche models. Projected‐related niche overlaps were then calculated using projected distributions and the corresponding climatic conditions. Results Average observed niche overlaps of congeneric pairwise species were relatively small: .124, .211 and .109 for all, herbaceous and woody species, respectively. Both observed and projected‐related niche overlaps had significant negative relationships with divergence times of intercontinental congeneric pairwise species, with niche overlap for herbaceous species being higher than that for woody plants when controlling for divergence times. Main conclusions We conclude that the significant negative relationships between niche overlap and divergence times of congeneric pairwise species confirm niche conservatism among species of EAS–ENA disjunct plants and that the extent of niche conservatism is slightly different for herbaceous and woody plants. These findings suggest the potential role of allopatric speciation in EAS, and could help to understand the evolutionary history and the Asian‐bias diversity pattern of the EAS–ENA disjunct plants.

Effects of climate and topography on the diversity anomaly of plants disjunctly distributed in eastern Asia and eastern North America - Xue Yin; Hong Qian; Xinghua Sui; Minhua Zhang; Lingfeng Mao; Jens‐Christian Svenning; Robert E. Ricklefs; Fangliang He (Global Ecology and Biogeography, 2021)
Aim Differences in physiography have been proposed to explain the diversity anomaly for vascular plants between environmentally similar regions of eastern Asia (EAS) and eastern North America (ENA). Here, we use plant species within disjunct genera to examine whether differences in topography contribute to the diversity anomaly and whether the richness–environment relationships differ between regions. Disjunct plants are used to ensure that the diversity anomaly relates to post‐disjunction evolution and diversification rather than regional differences in clade ages or immigration. Location EAS and ENA. Time period Current. Major taxa studied Plant taxa disjunctly distributed in EAS and ENA. Methods We compiled county‐level plant distribution data, and calculated species richness and variables of topography and climate within unit grid cells. We compared estimated coefficients of region effects among models, where richness was fitted with or without topography and climate. Topography and climate were also used to separately model within‐region spatial diversity patterns using spatial simultaneous autoregressive error models. Results The coefficients of region effects varied from −.776 for the model only including region to −.309 when topography was controlled for, but remained significant. Climate dominated the spatial diversity patterns in ENA. In contrast, the influence of climate (14.2%) on species richness was weaker than that of topography (18.3%) in the warm area of EAS. Relations to elevation and temperature varied between regions, shifting between positive and negative relationships in several cases. Main conclusions Our results demonstrate that variability in local topography contributes to the strong regional anomaly in plant species richness between EAS and ENA. Nevertheless, the diversity anomaly persists after controlling for local topography and climate. EAS and ENA also exhibit contrasting richness–environment relationships, providing another divergent aspect between the EAS–ENA disjunct floras. Our findings highlight that regional differences in topography or other environmental factors may underlie the diversity anomaly.

Faster recovery of soil biodiversity in native species mixture than in Eucalyptus monoculture after 60 years afforestation in tropical degraded coastal terraces - Wenjia Wu; Luhui Kuang; Yue Li; Lingfeng He; Zhijian Mou; Faming Wang; Jing Zhang; Jun Wang; Zhi’an Li; Hans Lambers; Jordi Sardans; Josep Peñuelas; et al. (Global Change Biology, 2021)
Afforestation is an effective method to restore degraded land. Afforestation methods vary in their effects on ecosystem multifunctionality, but their effects on soil biodiversity have been largely overlooked. Here, we mapped the biodiversity and functioning of multiple soil organism groups resulting from diverse afforestation methods in tropical coastal terraces. Sixty years after afforestation from bare land (BL), plant species richness and the abundance of plant litter (398 ± 85 g m −2 ) and plant biomass (179 ± 3.7 t ha −1 ) in native tree species mixtures (MF) were restored to the level of native forests (NF; 287 ± 21 g m −2 and 243.0 ± 33 t ha −1 , respectively), while Eucalyptus monoculture (EP) only successfully restored the litter mass (388 ± 43 g m −2 ) to the level of NF. Soil fertility in EP and MF was increased but remained lower than in NF. For example, soil nitrogen and phosphorus concentrations in MF (1.2 ± 0.2 g kg −1 and 408 ± 49 mg kg −1 , respectively; p −1 and 523 ± 24 mg kg −1 , respectively; p

Assessment of uranium migration and pollution sources in river sediments of the Ili River Basin using multiply statistical techniques - Lingfeng Dong; Zhanfei He; Fan Zhang; Tao Xu; Jingyi Wu; Kaifang Yan; Xiangliang Pan; Daoyong Zhang (Environmental Science and Pollution Research, 2021)

Initial results of centralized autonomous orbit determination of the new-generation BDS satellites with inter-satellite link measurements - Chengpan Tang; Xiaogong Hu; Shanshi Zhou; Li Liu; Junyang Pan; Liucheng Chen; Rui Guo; Lingfeng Zhu; Guangming Hu; Xiaojie Li; Feng He; Zhiqiao Chang (Journal of Geodesy, 2018)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)